Studi Perbandingan Prestasi Belajar Matematika Menggunakan Model Pembelajaran Discovery Learning dan The Power of Two - Amrullah; Anisyah Isni Muthia; Laila Hayati; Eka Kurniawan (Jurnal Riset Pendidikan Matematika Jakarta, 2022)
This study aims to find out the differences in the learning achievements of students who are taught using the Discovery Learning learning model with students who are taught using the Power of Two learning model. This type of research is Quasi Eksperiment. Sampling techniques use Probability Sampling by means of Cluster Random Sampling so that class VIII B is obtained as a Discovery Learning class and class VIII C as the Power of two class. Data collection techniques are carried out by means of obervasi and write tests. The data was analyzed using a normality test, a homogeneity test and an independent sample t test. From the results of the study obtained (i) The average cognitive learning outcome (post-test) of class VIII B students with discovery learning model of 79.22 and the average cognitive learning results (post-test) of class VIII C students with the learning model of the Power of Two of 79.11. (ii) there is no significant difference between a student's mathematical learning achievement after being taught using the Dicovery Learning model and the Power of Two.